2016
DOI: 10.4103/2231-0762.183104
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of antimicrobial effect of herbal root canal irrigants (Morinda citrifolia, Azadirachta indica, Aloe vera) with sodium hypochlorite: An in vitro study

Abstract: Aim and Objectives:Successful root canal treatment involves the complete elimination of microorganism from the root canal and the three-dimensional obturation of the canal space. Enterococcus faecalis is the most commonly found bacteria in failed root canal. Chemical irrigation of canals along with biomechanical preparation helps in the elimination of microorganisms. The present study was aimed to evaluate the antimicrobial effect of herbal root canal irrigants (Morinda citrifolia, Azadirachta indica extract, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 10 publications
3
47
0
3
Order By: Relevance
“…Similarly, Babaji et al. () also found that the extract of the M. citrifolia fruit with sodium hypochlorite had antimicrobial activity against Enterococcus faecalis . The results indicate that the extract of the fruit of M. citrifolia has high potential of use as an herbal root canal irrigant.…”
Section: Phytotherapic Propertiesmentioning
confidence: 87%
“…Similarly, Babaji et al. () also found that the extract of the M. citrifolia fruit with sodium hypochlorite had antimicrobial activity against Enterococcus faecalis . The results indicate that the extract of the fruit of M. citrifolia has high potential of use as an herbal root canal irrigant.…”
Section: Phytotherapic Propertiesmentioning
confidence: 87%
“…Leaf, fruit and aerial part of M. citrifolia exhibit antimicrobial effect against Escherichia coli, Staphylococcus aureus, Candida albicans , Aspergillus niger, Pseudomonas aeruginosa, Proteus morgaii, Bacillus subtilis, Helicobacter pylori , Enterococcus faecalis , Salmonella and Shigella species (Jainkittivong et al, ; Candida et al, ; Choudhary et al, ; Dhivya, & Santhy, ; Chaitanya et al, ; Babaji, Jagtap, & Lau, ; Bhardwaj, Velmurugan, & Sumitha, ; Usha et al, ; Banerjee, Johnson, Csiszar, Wansley, & McGeady, ). The morinquinone isolated from the stems of M. elliptica possesses weak antimicrobial activity against S. aureus and a methicillin‐resistant S. aureus .…”
Section: Pharmacology Of Indian Morinda Speciesmentioning
confidence: 99%
“…After being the magical antibacterial irrigant over the years, NaOCL is the best choice when the bacterial reduction is required [23, 24]. However, its cytotoxic effects restrict its use in certain biological experiences; efforts have been made to find alternatives [25, 26]. The traditional irrigation approaches are efficient in cleaning root canals coronally, but less effective apically [27].…”
Section: Discussionmentioning
confidence: 99%